The educational gradient in dental caries experience in Northern- Norway: a cross-sectional study from the seventh survey of the Tromsø study - Silje Navjord Moltubakk; Birgitta Jönsson; Marko Lukic; Lina Stangvaltaite-Mouhat (BMC Oral Health, 2023)
Abstract Background Although, studies from Norway indicate a reduction in dental caries experience, in Northern-Norway this non-communicable oral condition is still prevalent. There is conflicting evidence of presence of social inequalities in dental caries in an adult population. Therefore, the aim of this study was to assess an association between educational level and dental caries experience in adults in urban Tromsø municipality, Northern-Norway, using The World Health Organization (WHO) Commission on Social Determinants of Health (CSDH) framework of health determinants. Methods Data from 3752 participants having recorded dental caries status and educational level in the seventh survey of the Tromsø Study: Tromsø7 were included. Dental status was examined clinically as decayed-, missing-, filled-teeth (DMFT score). For statistical analyses DMFT score was grouped into lower (DMFT < 19) and higher (DMFT ≥ 20). Educational level was obtained from a questionnaire and categorized as primary/partly secondary education, upper secondary education, tertiary education, short and tertiary education, long. Data on social and intermediary determinants was also self-reported. Univariable and multivariable binary logistic regression analyses were applied. Result This study included 1939 (52%) women and the mean age of the participants was 57.11. The mean DMFT score was 18.03. The odds of having higher DMFT score followed a gradient based on educational level. Participants who reported lower than secondary education had 2.06 -fold increased odds of having higher DMFT score than those with tertiary education, long (OR: 2.06, 95% CI: 1.50–2.83). Those with upper secondary education had 60% higher odds of having higher DMFT score (OR: 1.60, 95% CI: 1.21–2.11), and those with tertiary education, short had 66% higher odds of having higher DMFT score (OR: 1.66, 95% CI: 1.24–2.22). Conclusion The current cross-sectional study suggested an educational gradient in dental caries experience in an adult population of Northern- ...